Acute cocoa Flavanols intake has minimal effects on exercise-induced oxidative stress and nitric oxide production in healthy cyclists: a randomized controlled trial - Lieselot Decroix; Cajsa Tonoli; Danusa Dias Soares; Amandine Descat; Marie-José Drittij-Reijnders; Antje R. Weseler; Aalt Bast; Wilhelm Stahl; Elsa Heyman; Romain Meeusen (Journal of the International Society of Sports Nutrition, 2017)
Background Cocoa flavanols (CF) can stimulate vasodilation by improved nitric oxide (NO) synthesis and have antioxidant and anti-inflammatory capacities. This study aimed to examine whether acute CF intake can affect exercise-induced changes in antioxidant capacity, oxidative stress, inflammation and NO production, as well as exercise performance and recovery in well-trained cyclists. Methods Twelve well-trained male cyclists (mean ± SD age, VO2max: 30 ± 3 years, 63.0 ± 3.5 ml/kg/min) participated in this randomized, double-blind, cross over study. On 2 separate occasions, subjects performed two 30-min time trials 1.5 (TT1) and 3 (TT2) hours after CF (900 mg CF) or placebo (PL, 13 mg CF) intake, interposed by passive rest. Lactate, glucose, heartrate, rating of perceived exertion (RPE) and power output were measured during the TTs. Blood was drawn at baseline, before and after each TT and analyzed for epicatechin serum concentrations, trolox equivalent antioxidative capacity (TEAC), uric acid (UA), malonaldehyde (MDA), L-arginine/ADMA, citrulline, interleukin (IL)-1, IL-6 and tumor necrosis factor (TNF)-α plasma concentrations. Relative changes in blood markers and pacing strategy during TT were analysed by repeated measured ANOVA. TT performance was compared between PL and CF by paired t-test. Results Epicatechin concentrations were increased by CF intake. Exercise-induced increase in TEAC/UA was improved by CF intake (F(1) = 5.57; p = .038) (post-TT1: PL: 113.34 ± 3.9%, CF: 117.64 ± 3.96%, post-TT2: PL: 108.59 ± 3.95%, CF: 123.72 ± 7.4% to baseline), while exercise-induced increases in MDA, IL-1 and IL-6 were not affected by CF intake. TNF-α was unaltered by exercise and by CF. Exercise-induced decreases in L-arginine/ADMA and increases in citrulline were not affected by CF intake. TT1 and TT2 performance and exercise-induced physiological changes were unaffected by CF intake. Conclusion Acute CF intake increased total antioxidant capacity in rest and during exercise, but did not affect exercise-induced lipid peroxidation, inflammation, nor NO production in healthy athletes. Acute CF intake did not improve TT performance and recovery. Trial registration ISRCTN32875, 21-11-2016, retrospectively registered.